Pengaruh Model Problem Based Learning Terhadap Hasil Belajar IPA Siswa Kelas V Sekolah Dasar - indriyanti, weni; fitria, yanti; mansur, ajo (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
This study aimed to determine the effect of learning model Problem Based Learning  on  learning  outcomes  fifth  grade  science  students  14  Pasaman,  district Pasaman, Pasaman Barat Regency  Academic  Year  2017/2018.  This  research  is  a quasi  experimental  research  with  the  research  design  used  is  Non  Equivalent Control Group Design. The sample is determined by Purposive sampling technique. The sample in this research is the students of class V in State Elementary School 14 Pasaman.  The  results  of  this  study  obtained  the  average  value  of  the experimental class using the problem-based learning model higher 83,36 than the control class using conventional learning 77,12 Based on the calculation of t test obtained that tcount 2.93 is greater than ttable 1,677 indicates that theris a significant effect on students' learning outcomes. Based on the results of this study  can  be  concluded  that  the  model  of  learning  Problem  Based  Learning influence on the learning outcomes of science class V SDN 14 Pasaman Pasaman District.